(untitled) (Journal of actual problems of jurisprudence, 2019)
In given article the author considers problems of legal maintenance of power safety and steady development. The author holds the opinion that in the decision of legal problems of power safety and economic steady development it is necessary to take into account legal tools of preservation of the environment and for the decision of these problems bases on the international acts.